LETMD1 is required for mitochondrial structure and thermogenic function of brown adipocytes. Issue 11 (20th October 2021) - Snyder, Madigan M.; Yue, Feng; Zhang, Lijia; Shang, Renjie; Qiu, Jiamin; Chen, Jingjuan; Kim, Kun Ho; Peng, Ying; Oprescu, Stephanie N.; Donkin, Shawn S.; Bi, Pengpeng; Kuang, Shihuan
Abstract: Obesity and metabolic disorders caused by energy surplus pose an increasing concern within the global population. Brown adipose tissue (BAT) dissipates energy through mitochondrial non‐shivering thermogenesis, thus representing a powerful agent against obesity. Here we explore the novel role of a mitochondrial outer membrane protein, LETM1‐domain containing 1 (LETMD1), in BAT. We generated a knockout ( Letmd1 KO ) mouse model and analyzed BAT morphology, function and gene expression under various physiological conditions. While the Letmd1 KO mice are born normally and have normal morphology and body weight, they lose multilocular brown adipocytes completely and have diminished mitochondrial abundance, DNA copy number, cristae structure, and thermogenic gene expression in the intrascapular BAT, associated with elevated reactive oxidative stress. In consequence, the Letmd1 KO mice fail to maintain body temperature in response to acute cold exposure without food and become hypothermic within 4 h. Although the cold‐exposed Letmd1 KO mice can maintain body temperature in the presence of food, they cannot upregulate expression of uncoupling protein 1 (UCP1) and convert white to beige adipocytes, nor can they respond to adrenergic stimulation. These results demonstrate that LETMD1 is essential for mitochondrial structure and function, and thermogenesis of brown adipocytes.